A study of employee perception toward performance appraisal in the Pizza Hut and KFC / Liliyan Said - Said, Liliyan (2009)
This research is investigating employee perception toward performance appraisal in the Pizza Hut and KFC restaurant. The objectives of the research included to identify the most influential indicators for employee perception toward performance appraisal in the Pizza Hut and KFC, to identify employee perception towards the effectiveness of the four indicators in performance appraisal in the Pizza Hut and KFC, and to identify employee job satisfaction in the Pizza Hut and KFC. The implication for his research shows that job satisfaction is the most influential factors effect employee perception toward performance appraisal in the organization. It is shows that, the employee have a positive perception toward performance appraisal applied in the organization. if the implication shows employee perception toward performance appraisal is negative, it will affect the employee performance. Employee will become unsatisfied with their job performance.